2004
DOI: 10.1073/pnas.0401331101
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the Deinococcus radiodurans single-stranded DNA-binding protein suggests a mechanism for coping with DNA damage

Abstract: Single-stranded DNA (ssDNA)-binding (SSB) proteins are uniformly required to bind and protect single-stranded intermediates in DNA metabolic pathways. All bacterial and eukaryotic SSB proteins studied to date oligomerize to assemble four copies of a conserved domain, called an oligonucleotide͞oligosaccharide-binding (OB) fold, that cooperate in nonspecific ssDNA binding. The vast majority of bacterial SSB family members function as homotetramers, with each monomer contributing a single OB fold. However, SSB pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
119
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 33 publications
(37 reference statements)
8
119
0
Order By: Relevance
“…Because the homodimeric D/T group SSBs have non-identical OB domains present in each monomer, it has been suggested that the DNA binding properties of each domain may differ for this group of SSBs (15). A crystallographic approach was taken to determine the ssDNA-bound structure of DrSSB, the founding member of the D/T group homodimeric SSBs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the homodimeric D/T group SSBs have non-identical OB domains present in each monomer, it has been suggested that the DNA binding properties of each domain may differ for this group of SSBs (15). A crystallographic approach was taken to determine the ssDNA-bound structure of DrSSB, the founding member of the D/T group homodimeric SSBs.…”
Section: Resultsmentioning
confidence: 99%
“…Dimerization places the four OB domains in very similar positions to that found in homotetrameric SSBs, which could indicate that both classes of bacterial SSBs bind ssDNA in a conserved manner. However, because the OB domains within D/T SSB monomers are not identical in sequence, the N-and C-terminal OB domains could bind ssDNA differently (15). Structural data mapping the ssDNA binding sites of a number of homotetrameric SSBs are available (19 -22), but high resolution structures of D/T SSBs in complex with ssDNA have not been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of several prokaryotic ssDNA-binding proteins have been solved (4)(5)(6)(7)(8)(9). Although these proteins do not have sequence homology, their structures share a common oligosaccharide/oligonucleotide-binding fold (OB-fold), suggesting that they have a similar mode of action.…”
mentioning
confidence: 99%
“…Approximately the first 120 N-terminal residues comprise the OB/SSB fold with conserved structure whereas the rest of the protein has been implicated in interacting with other protein partners and in some cases has been disordered in the crystal structures. Numerous prior efforts have reported in detail the crystal structures of functionally annotated SSBs, [12][13][14][15][16][17][18][19][20][21][22][23] presented comparative analysis of homologous SSBs 20,24 and reported on structures of their protein-DNA complexes. 25,26 An electrophoretic mobility shift assay confirmed that MPN554 binds to a 39-mer single-stranded DNA.…”
mentioning
confidence: 99%